Policy Development Framework for Operations Management During Crises: A Multiple Case Study of Nueva Ecija Cooperatives Amid the COVID-19 Pandemic - James Michael Alcaide Dalde (WPOM : Working Papers on Operations Management)
The COVID-19 pandemic presented unprecedented challenges to businesses worldwide, including cooperatives in Nueva Ecija, Philippines. These organizations faced unique trials due to their distinct structure and operations. This study aims to understand the crisis management strategies employed by these cooperatives during the pandemic. Utilizing Mitroff's (1994) five stages of crisis, resilience theory, and stakeholder theory, the research provides a comprehensive view of how cooperatives navigated each stage of the crisis.